La flaneuse en la historia de la cultura occidental - Cuvardic García, Dorde (2012)
This article summarizes the state of international research on the figure of the flaneuse. Some expressions of the flaneuse are also researched through the history of literature, as well as investigating the different social practices in which they can be involved. From an historical category perspective, the initial research on the flaneuse denied the possibility of her existence, in terms of the different access men and women have experienced on public spaces in the West. From a conceptual category perspective, other researchers have proposed the existence of different types of flaneuses (the female passer-by enjoying free access to public spaces, the female social researcher, the female pollster, the female social worker, the female consumer, the female movie goer). Now, research analyzes different experiences women have expressed about their access to public spaces in several types of autobiographical writings: in this case, the passante, object of the flaneur’s visual pleasure, gives way to the flaneuse, the woman expressing her own subjectivity.